Death and mooring, representation systems - Carlos Rodríguez Rodríguez (Universidad de Alicante, 2012)
The present work is a contribution from the point of view of the Anthropology to the analysis of the bereavement, from two complementary focuses: in first place, we attracted attention on the importance of the cosmology that the different human groups have on the death and in second place the importance that, based an opinion on those [cosmologies] on the death, they have the different systems of ritualitation with object of composing the lost of one of their members in the group and help to those that they remain to take on their paper of deed, and of the new lists that the obit produces in the social structure. The death represents and condenses the courage's of each society, you/he/she/it abridge the explanation of the life, their sense and the of the group, the explanations on the concept of death are so much like human groups, from those in those that the death is a rebirth to a new life until the one which the be been you hes he it reinstate to the group, and you he she it unite again I he she it you to the group am already like of each one of their members or in those in those that the death gives place to a new life. How could the individual and the group take on the void and the horror of the do you/he/she/it swim? Only within their own frame cosmology, their own conception of the death, in order to separate the death of the life and psychological to the family and to the remainder of the group in the new situation.